2017
DOI: 10.1002/2017wr020375
|View full text |Cite
|
Sign up to set email alerts
|

Complex networks of functional connectivity in a wetland reconnected to its floodplain

Abstract: Disturbances such as fire or flood, in addition to changing the local magnitude of ecological, hydrological, or biogeochemical processes, can also change their functional connectivity—how those processes interact in space. Complex networks offer promise for quantifying functional connectivity in watersheds. The approach resolves connections between nodes in space based on statistical similarities in perturbation signals (derived from solute time series) and is sensitive to a wider range of timescales than trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…Although the direction of flow from the S‐152 was generally radial (as expected from a point source), dye deployed at the S‐152 confirmed findings by Larsen et al (), showing a preferential flow east toward the control sites C1 and Z6‐1 (Eric Cline, SFWMD, personal communication; Sklar & Dreschel, ). The apparent contradiction between greater hydrologic connectivity east of S‐152 (Larsen et al, ) but greater sediment source changes to the south (based on biomarker changes) could potentially be explained by the differential movement of dissolved versus particulate forms in the water column. Hydrologic connectivity quantified by Larsen et al () is based on both dissolved and particulate water column constituents (and only dissolved constituents for dye studies), whereas the change in Paq reflects movement of only particulate, macrophyte‐derived organic matter.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…Although the direction of flow from the S‐152 was generally radial (as expected from a point source), dye deployed at the S‐152 confirmed findings by Larsen et al (), showing a preferential flow east toward the control sites C1 and Z6‐1 (Eric Cline, SFWMD, personal communication; Sklar & Dreschel, ). The apparent contradiction between greater hydrologic connectivity east of S‐152 (Larsen et al, ) but greater sediment source changes to the south (based on biomarker changes) could potentially be explained by the differential movement of dissolved versus particulate forms in the water column. Hydrologic connectivity quantified by Larsen et al () is based on both dissolved and particulate water column constituents (and only dissolved constituents for dye studies), whereas the change in Paq reflects movement of only particulate, macrophyte‐derived organic matter.…”
Section: Resultssupporting
confidence: 79%
“…PC2 may also reflect the long‐term decline in HBI values over the study period, observed in both habitats (Figure S3). The underlying driver for this change remains unclear but may be a response to a fire in June 2011, which burned ridges throughout the study area (described in Larsen et al, ), or by a flow‐mediated change in slough vegetation. The latter, however, seems less likely as such changes were mainly evident in a small subset of high‐flowing sites nearest the S‐152 (Saunders, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations